PERILAKU TRENGGILING (Manis javanica, Desmarest, 1822) DAN KEMUNGKINAN PENANGKARANNYA - Burhanuddin Masy'ud; Novriyanti .; M. Bismark (Media Konservasi, 2011)
Pangolin (Manis javanica, Desmarest 1822) has believed by many peoples as  food and medicine who have a high economic value, so demand of pangolin tend increase. Wild harvesting  from natural habitat are  the way always  used to  supply of   demand,  and this was affecting to wild population has been decrease significantly. Captive breeding programs in the ex situ area is  the best alternative solution to support the demand sustainability and its conservastion in natural habitat. The question is, “ did success possibilities to captive breeding? Based on the study have been done about animal behaviour and implementation of some technical of captive breeding program,we would like to say that the captive breeing program of pangolin could be success. Key words: pangolin, behaviour, daily activities, captive breeding